2008
DOI: 10.1002/mpr.264
|View full text |Cite
|
Sign up to set email alerts
|

Personality dimensions measured using the Temperament and Character Inventory (TCI) and NEO‐FFI on a Polish sample

Abstract: TCI scores for persons with excluded mental disease are highly changeable depending on age, sex and education. Adjusted to sex and age scores NEO-FFI corresponded better than TCI to stability and genetic determinants of human personality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
9
1
1
Order By: Relevance
“…As regards the effect of demographic variables on temperament and character, we found an inverse relationship between age and NS score (Chen et al, 2013;Cloninger, 1994a;Cloninger et al, 1993;Mikolajczyk et al, 2008), but, in contrast with previous literature (Gutierrez-Zotes et al, 2004;Hansenne et al, 2005;Pelissolo and Lepine, 2000;Sasayama et al, 2011), our multivariate analyses found no independent effect of gender on any TCI dimension.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…As regards the effect of demographic variables on temperament and character, we found an inverse relationship between age and NS score (Chen et al, 2013;Cloninger, 1994a;Cloninger et al, 1993;Mikolajczyk et al, 2008), but, in contrast with previous literature (Gutierrez-Zotes et al, 2004;Hansenne et al, 2005;Pelissolo and Lepine, 2000;Sasayama et al, 2011), our multivariate analyses found no independent effect of gender on any TCI dimension.…”
Section: Discussioncontrasting
confidence: 80%
“…Since both age (Chen et al, 2013;Cloninger, 1994a;Cloninger et al, 1993;Mikolajczyk et al, 2008) and gender (Gutierrez-Zotes et al, 2004;Hansenne et al, 2005;Pelissolo and Lepine, 2000), were previously reported to affect temperament and character, a series of univariate analyses was performed to test their associations with TCI dimensions. Age resulted to have a mild negative correlation with NS (r= -0.25; p<.0001) and RD (r= -0.16; p<.0001), and a mild positive correlation with ST (r= 0.19; p<.0001), while females resulted to have significantly higher scores on HA (51.41±9.67 vs 47.93±10.11; t= -3.65; p=.0003).…”
Section: Differences In Temperament and Character Among Groupsmentioning
confidence: 99%
“…However, meta-analyzes present numerous methodological and statistical force problems. In particular, as far as we are concerned, they cannot discriminate the presence of certain confounding factors such as socio-demographic variables ( Wasek and Endicott, 1983 ; Cloninger, 1992 ; Cloninger et al, 1993 ; Peselow et al, 1995 ; Gutierrez-Zotes et al, 2004 ; Hansenne et al, 2005 ; Mikołajczyk et al, 2008 ; Chen et al, 2013 ) and the number of psychopathological episodes in the arc of life ( Hirschfeld et al, 1989 ; Zaninotto et al, 2015 ; Paolini et al, 2016 ). Finally, meta-analyzes should also include follow-up studies as these can help to disentangle the “state-trait” effect to determine if a specific character vulnerability model exists for the development of affective disorders ( Farmer et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in that previous study personality traits were obtained from the Neo Personality Inventory (NEO) (39) and from the Cloninger's Temperament and Character Inventory (TCI) (40) which provide a sense of some basic traits that are central to the description of general personality. Unlike the SCID-II scale (23) used in the current study, the NEO and TCI scales do not intend to measure the pathological functioning of personality and, in these scales, the presence of personality traits is not necessarily related to impairment (41,42).…”
Section: Discussionmentioning
confidence: 99%